Maternal mortality in the Maternity Hospital of Lima. Years 1960-1969. - Villa Javier, Félix (2015)
In the present work has been done a full review of all maternal deaths in the Maternity Hospital of Lima, from January 1st 1960 to December 31, 1969, in order to specify certain aspects of national interest and to point at a time, the current casuistics of said hospital.